Uso racional de antibióticos betalactámicos en pacientes de medicina interna y cirugía del Hospital María Lorena Serrano Aguilar. - Macas Paltin, Katherine Lisbeth (2017)
The present investigation was carried out at the María Lorena Serrano Aguilar Basic Hospital El Guabo, El Oro province, during the months of March, April and May of 2017 in which the hospitalized patients belonging to two basic specialties that the public institution counts as the area of internal medicine and surgery. The purpose of this research is to promote the rational use of betalactam antibiotics through the application of unit dose in patients hospitalized in internal medicine and surgery in order to provide a quality service to the patient. To do this, it was necessary to investigate the diagnoses presented by the patients according to the areas of internal medicine and surgery, then identified the most prescribed betalactam antibiotics pertaining to the study areas, followed by the application of a unit dose to the patients who were prescribed betalactam antibiotics and finally was developed a registry of stabilization of the betalactam antibiotics that are in the stock of the department of institutional pharmacy. Inclusion criteria that were taken in this study were patients aged 16 to 64 years hospitalized in the area of internal medicine and surgery in the months of march, april and may who were prescribed betalactam antibiotics. The research uses the scientific method, it is approached according to the type of prospective cross-sectional descriptive study. The population consisted of 100 hospitalizations, of which a sample of 80 patients were included, including the two specialties. The technique of data collection used was documentary using as a tool a model data collection form template prepared by the authors, validated by the thesis supervisor and head of the department of the institutional pharmacy area of the research site. The diagnoses presented by patients in the area of internal medicine were: diabetic foot infection (35%), severe pneumonia (23%), acute pyelonephritis (20%), intrahospital pneumonia (13%), and cellulite (9%) while in surgery they were: acute cholecystitis (28%), acute appendicitis (24%), peritonitis (20%), intestinal obstruction (15%), abscess of mammary glands (10%) and liver abscess (3%). Among the most prescribed betalactam antibiotics in the area of internal medicine were ceftriaxone (30%), ceftazolin (25%), ceftazidime (20%), amoxicillin/ clavulanic acid (11%), ampicillin/sulbactam (11%) and benzylpenicillin G crystalline (3%), with respect to the surgery area were ampicillin/ sulbactam (37%), cefazolin (23%), ceftriaxone (23%), ceftazidime (10%) and amoxicillin/ clavulanic acid (7%). The application of unit dose to patients who were prescribed betalactam antibiotics in the two areas was perfomed based on their respective normalization. It was concluded that in the area of medicine, the diagnoses were chronic, while those of acute surgery with urgent surgical operations, regarding the type of the prescription of the betalactam antibiotics in the area of internal medicine and sugery was 75% rational and 25% irrational, due to the fact that microbiological analysis (antibiogram) was not observed an important aspect for a correct selection of the antibiotic.